Association between periodontitis and endometriosis: a bidirectional Mendelian randomization study - Jin, Bilun; Wang, Pengfei; Liu, Peiqi; Wang, Yijie; Guo, Yi; Wang, Chenxu; Jia, Yue; Zou, Rui; Dong, Shaojie; Niu, Lin (Frontiers in Endocrinology, 2024)
Introduction A potential association between periodontitis and endometriosis has been indicated in previous observational studies. Nevertheless, the causal link between these two disorders has not been clarified. Methods Based on publicly available genome-wide association study (GWAS) summary datasets, we conducted a bidirectional Mendelian randomization (MR) study to investigate the relationship between periodontitis and endometriosis and its subtypes. Single nucleotide polymorphisms (SNPs) strongly associated with candidate exposures at the genome-wide significance level (P < 5 × 10−8) were selected as instrumental variables (IVs). The inverse variance-weighted regression (IVW) was performed to estimate the causal effect of periodontitis on endometriosis. We further conducted two sensitivity analyses, MR-Egger and weighted median, to test the validity of our findings. The main results were replicated via data from the UK Biobank. Finally, a reverse MR analysis was performed to evaluate the possibility of reverse causality. Results The IVW method suggested that periodontitis was positively associated with endometriosis of the pelvic peritoneum (OR = 1.079, 95% CI = 1.016 to 1.146, P = 0.014). No causal association was indicated between periodontitis and other subtypes of endometriosis. In reversed analyses, no causal association between endometriosis or its subtypes and periodontitis was found. Conclusions Our study provided genetic evidence on the causal relationship between periodontitis and endometriosis of the pelvic peritoneum. More studies are necessary to explore the underlying mechanisms.